The marginal benefits of healthcare spending in the Netherlands: Estimating cost‐effectiveness thresholds using a translog production function. (30th August 2019) - Stadhouders, Niek; Koolman, Xander; van Dijk, Christel; Jeurissen, Patrick; Adang, Eddy
Abstract: New technologies may displace existing, higher‐value care under a fixed budget. Countries aim to curtail adoption of low‐value technologies, for example, by installing cost‐effectiveness thresholds. Our objective is to estimate the opportunity cost of hospital care to identify a threshold value for the Netherlands. To this aim, we combine claims data, mortality data and quality of life questionnaires from 2012 to 2014 for 11, 000 patient groups to obtain quality‐adjusted life‐year (QALY) outcomes and spending. Using a fixed effects translog model, we estimate that a 1% increase in hospital spending on average increases QALY outcomes by 0.2%. This implies a threshold of €73, 600 per QALY, with 95% confidence intervals ranging from €53, 000 to €94, 000 per QALY. The results stipulate that new technologies with incremental cost effectiveness ratios exceeding the Dutch upper reference value of €80, 000 may indeed displace more valuable care.